Fabrication of Al–Cu–Fe quasicrystal reinforced 6082 aluminium matrix nanocomposites through mechanical milling and spark plasma sintering - Shadangi Y.; Sharma S.; Shivam V.; Basu J.; Chattopadhyay K.; Majumdar B.; Mukhopadhyay N.K. (My University, 2025)
In the present investigation, attempts were made to study the effect of Al–Cu–Fe (40 vol%) quasicrystalline (QC) reinforcement on the structure, morphology and phase composition of 6082 Al matrix nanocomposites (AMCs) processed through mechanical milling (MM) and spark plasma sintering (SPS). The characterization of these MM and SPSed AMCs was done through X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM). The MM induces microstructural refinement of matrix and partial structural transformation of QC phase to Al13Fe4 approximant phase (a = 1.549 nm, b = 0.808 nm, c = 1.248 nm, α = β = 90°, γ = 107.72°; mC102; C2/m). The presence of (311111) diffraction peak of the QC phase in AMCs confirms the existence of face-centred QC phase even after 50 h of MM. The consolidation of Al-QC at 450 °C (723 K) and 550 °C (823 K) results in the fabrication of AMCs having a density of 2.921 and 3.319 g cm−3 respectively. The compressive yield strength and ultimate strength of these AMCs is ∼519 MPa and 639 MPa respectively. The enhancement in the mechanical properties may be attributed to strong interfacial bonding of the Al matrix and QC reinforcement due to interfacial reactions. © 2020 Elsevier B.V.